High-Altitude Genetic Selection and Genome-Wide Association Analysis of Yield-Related Traits in Elymus sibiricus L. Using SLAF Sequencing - Zhang, Zongyu; Zheng, Yuying; Zhang, Junchao; Wang, Na; Wang, Yanrong; Liu, Wenhui; Bai, Shiqie; Xie, Wengang (Frontiers in Plant Science, 2022)
The genetic adaptations to harsh climatic conditions in high altitudes and genetic basis of important agronomic traits are poorly understood in Elymus sibiricus L. In this study, an association population of 210 genotypes was used for population structure, selective sweep analysis, and genome-wide association study (GWAS) based on 88,506 single nucleotide polymorphisms (SNPs). We found 965 alleles under the natural selection of high-altitude, which included 7 hub genes involved in the response to ultraviolet (UV), and flavonoid and anthocyanin biosynthetic process based on the protein-protein interaction (PPI) analysis. Using a mixed linear model (MLM), the GWAS test identified a total of 1,825 significant loci associated with 12 agronomic traits. Based on the gene expression data of two wheat cultivars and the PPI analysis, we finally identified 12 hub genes. Especially, in plant height traits, the top hub gene (TOPLESS protein) encoding auxins and jasmonic acid signaling pathway, shoot apical meristem specification, and xylem and phloem pattern formation was highly overexpressed. These genes might play essential roles in controlling the growth and development of E. sibiricus. Therefore, this study provides fundamental insights relevant to hub genes, and will benefit molecular breeding and improvement in E. sibiricus and other Elymus species.